2012
DOI: 10.1371/journal.pone.0035880
|View full text |Cite
|
Sign up to set email alerts
|

MyD88 Associated ROS Generation Is Crucial for Lactobacillus Induced IL-12 Production in Macrophage

Abstract: It is well known that some strains of lactic acid bacteria (LAB) can induce IL-12 which plays an important role in modulating immune responses. However, the mechanisms by which LAB induce IL-12 production remain unclear. Here, we examine the role of toll-like receptors (TLR's) and reactive oxygen species (ROS) in IL-12 production by LAB stimulated peritoneal macrophages. Our results indicate that a TLR is not necessary for IL-12 induction by LAB, whilst the universal adaptor protein, MyD88, is essential. Speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 52 publications
(52 reference statements)
3
21
0
Order By: Relevance
“…Downstream of the TLR signaling, the MyD88 adapter molecule is known to be crucial for the secretion of proinflammatory cytokines, such as IL-12 and IL-18 (29,30). MyD88 is involved in the downstream signaling of TLR4 and TLR9.…”
Section: Discussionmentioning
confidence: 99%
“…Downstream of the TLR signaling, the MyD88 adapter molecule is known to be crucial for the secretion of proinflammatory cytokines, such as IL-12 and IL-18 (29,30). MyD88 is involved in the downstream signaling of TLR4 and TLR9.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been noted that the activity of LAB stimulating the immune system is important (14,15,(20)(21)(22)(23). Yogurt is an example of fermented food with LAB.…”
Section: Screening Lab Activating Innate Immunity As a Yogurt Startermentioning
confidence: 99%
“…IFN-␥ signaling has been shown to modulate NO and ROS production (21)(22)(23)(24). These two phagosomal enzymes are indicators of the innate inflammatory response to microbial infection.…”
Section: Myd88mentioning
confidence: 99%
“…Both MyD88 and Card9 are required for differentiation and development of Th1 and Th17 immunity in Coccidioides-infected lungs (18,19). MyD88-and Card9-mediated signal pathways also facilitate microbe-induced production of reactive oxygen species (ROS) and nitric oxide (NO) (20)(21)(22)(23). However, in the case of pulmonary disease, we and others have shown that inducible NO synthase (iNOS) and NADPH oxidase 2 (NOX2), two enzymes required for ROS and NO production, have limited influence on the control of Coccidioides infection of lung tissue (24)(25)(26).…”
mentioning
confidence: 99%